Affective Dimension in Collaborative Information Seeking - Gonzalez-Ibanez, R (Springer International Publishing, 2015)
This chapter aims to reflect about the importance and challenges of research on the affective dimension in collaborative information seeking (CIS). This is achieved through three major parts. First, an overview of the relevance of the affective dimension is provided. Second, research on the affective dimension in individual information seeking in general, and CIS in particular is discussed. Finally, research approaches, challenges, and ethical aspects in this type of studies are discussed. This chapter hopes to encourage researchers to formulate new questions, hypotheses, and more importantly further investigate this interesting topic. © Springer International Publishing Switzerland 2015. All rights are reserved.